2020
DOI: 10.1037/spq0000357
|View full text |Cite
|
Sign up to set email alerts
|

Initial validation of the Classroom Management Observation Tool (CMOT).

Abstract: Effective classroom management is critical for student and teacher success. Because teachers receive limited preservice preparation and in-service support in classroom management, educational leaders (e.g., school psychologists, behavior coaches, mentor teachers, and administrators) need efficient and effective tools to identify teachers’ strengths and needs and to guide professional development. Current approaches to assess teachers’ classroom management are either (a) simple and efficient, but have unknown p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 36 publications
(53 reference statements)
0
6
0
Order By: Relevance
“…This unidimensional construct was best measured with three factors (i.e., preventive supports; feedback provision and engagement; and items related to rules, expectations, and consequences). This factor structure fits well and provides a thorough and comprehensible structure that is in accord with theoretical frameworks utilized to determine tool development (Simonsen et al, 2019(Simonsen et al, , 2020(Simonsen et al, , 2021) and items to be included in the current iteration of the CSC observation tool. Specifically, the factors were labeled based on Simonsen and colleagues' (2021) Tier 1 PCBS foundational practices as they relate to the classroom environment.…”
Section: Discussionmentioning
confidence: 65%
See 3 more Smart Citations
“…This unidimensional construct was best measured with three factors (i.e., preventive supports; feedback provision and engagement; and items related to rules, expectations, and consequences). This factor structure fits well and provides a thorough and comprehensible structure that is in accord with theoretical frameworks utilized to determine tool development (Simonsen et al, 2019(Simonsen et al, , 2020(Simonsen et al, , 2021) and items to be included in the current iteration of the CSC observation tool. Specifically, the factors were labeled based on Simonsen and colleagues' (2021) Tier 1 PCBS foundational practices as they relate to the classroom environment.…”
Section: Discussionmentioning
confidence: 65%
“…When certain items on the CSC were unclear or ambiguous, the team, including the experts in school PBIS, refined the items to ensure consistency across consultants using the observation tool. While Simonsen and colleagues’ (2019, 2020, 2021) Tier 1 guidelines served to highlight positive classroom practices and determine the potential constructs being measured, additional information was needed to determine general commonalities in the items observed. An EFA was then conducted to determine the factor structure of the classroom management observation tool utilizing observations of teachers’ classroom management.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Gregory et al (2016) found that a relationship between classroom coaching and racially equitable discipline rates was mediated by teachers’ use of instructional strategies promoting problem-solving and higher level thinking that communicate high expectations for students. Despite PBIS scholarship indicating the potential of these practices (e.g., Sugai & Horner, 2009), such practices lie outside the intended scope of commonly used measures of PBIS implementation fidelity (e.g., BoQ, Kincaid et al, 2010; Classroom Management Observation Tool, Simonsen et al, 2020; and School-Wide Evaluation Tool, Sugai et al, 2001).…”
Section: Discussionmentioning
confidence: 99%